Little Novels - Collins, Wilkie (Saga Egmont, 2022)
Collins's 1889 collection of fourteen short stories includes "Miss Morris and the Stranger," about a young governess and a fateful meeting, "Mr. Medhurst and the Princess," about two star-crossed lovers, and a dozen other tales involving love, social classes, money, and even ghosts.